2013
DOI: 10.1007/s00167-013-2460-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Staphylococcus aureus infection following open wedge high tibial osteotomy using antibiotic-impregnated calcium phosphate cement

Abstract: V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The management of deep SSI after MOWHTO reported in the past literature included the removal of internal fixation devices, debridement, and intravenous antibiotic injection. Some authors have proposed antibiotic-impregnated calcium phosphate cement insertion [8,32,33]. However, hardware removal can be problematic before bony union.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of deep SSI after MOWHTO reported in the past literature included the removal of internal fixation devices, debridement, and intravenous antibiotic injection. Some authors have proposed antibiotic-impregnated calcium phosphate cement insertion [8,32,33]. However, hardware removal can be problematic before bony union.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Postoperative deep SSI has been regarded as one of the most detrimental complications, which may lead to multiple revision surgeries, loss of correction degree, and nonunion. [8] However, few past reports have focused on this issue. The existing papers on the topic differ based on study design, patient collectives, implant selection, surgical technique, and investigation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible property inherent to MPCs which is desired, and often added to CPCs, is antibacterial activity. Although CPCs have antibiotics such as vancomycin added to the cement formulation, some MPCs may be naturally antibiotic. , Mestres et al observed cements of MgO + MNaHP salt or MNaHP/MAHP salt mixture exhibited bactericidal effects on S. sanguinis bacteria, whereas cements reacted with only MAHP salt exhibited growth inhibition but no bactericidal effects . The bactericidal effects were attributed to a combination of pH increase (up to 9.91) while the growth inhibition was attributed to acidic conditions and the release of Mg 2+ ions and reactive oxygen species from the remaining MgO.…”
Section: In Vitro Propertiesmentioning
confidence: 99%
“…Seki et al [ 7 ] successfully treated one case with hardware removal and filling of the osteotomy defect with vancomycin-impregnated, calcium phosphate cement associated with external fixation for 12 months and concomitant antibiotics for 3 months.…”
Section: Discussionmentioning
confidence: 99%